Implementasi Pembelajaran Berbasis HOTS dalam Meningkatkan Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran Matematika Sekolah Dasar - Irma Aprilia; Nadhifah Bayu; Nugraha Widya; Raditya Bagus; Shofia Lutfi (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
High Order Thinking Skill (HOTS) is a way of thinking for students at a higher cognitive level. This research aims to prove whether the implementation of HOTS-based learning has an impact in improving students' critical thinking skills in mathematics learning in elementary schools. The research method used is a literature review using the Google Scholar and Semantik Scholar databases for the 2020-2023 period. The HOTS-based learning model focuses on developing analyzing, evaluating and creating which refers to students' abilities in critical thinking. Based on the 8 selected articles, it shows that the implementation of HOTS learning in mathematics subjects can be implemented through learning models such as Game Based Learning or Digital Game Based Learning, teacher skills in implementing learning and developing assessments need to be considered. The application of HOTS learning is considered effective and able to improve students' critical thinking skills.